A Decentralized Authoritative Multiplayer Architecture for Games on the Edge - Tošić, Aleksandar; Vičič, Jernej (COMPUTING AND INFORMATICS, 2021)
With the ever growing number of edge devices, the idea of resource sharing systems is becoming more appealing. Multiplayer games are a growing area of interest due to the scalability issues of current client-server architectures. A paradigm shift from centralized to decentralized architectures that would allow greater scalability has gained a lot of interest within the industry and academic community. Research on peer to peer network protocols for multiplayer games was mainly focused on cheat detection. Previously proposed solutions address the cheat detection issues on a protocol level but do not provide a holistic solution for the architecture. Additionally, existing solutions introduce some level of centralization, which inherently introduces single point of failures. We propose a blockchain-based, completely decentralized architecture for edge devices with no single point of failure. Our solution relies on an innovative consensus mechanism based on verifiable delay functions that additionally allows the network to derive verifiable randomness. We present simulation results that show the assignment of players and referees to instances is pseudo-random, which inherently prevents collusion-based cheats and vulnerabilities.